Mathematical set and euler theories for formalizing new concept of spatial data modelling for hybrid 3D spatial objects - Abdul Rahman, Alias (Faculty of Geoinformation Science & Engineering, 2008)
This research attempts to explore two mathematical theories, namely, set and Euler theories for validation of 3D spatial objects which were generated or constructed from triangular irregular network. The relationship between the theories and spatial database development of the objects also investigated. Validating of 3D objects was restricted to 3D solid only, other primitives of validation such as solid and surface, solid and line, etc are not part of the study. The validation process of the 3D objects was carried out by developing a computer program based on C++ and couple with open source DBMS such as PostgreSQL. The results show that the theories could be utilised for validating 3D spatial objects.